UPAYA MENINGKATKAN PEMAHAMAN LAMBANG-LAMBANG PANCASILA DAN PENERAPANNYA DALAM KEHIDUPAN SEHARI-HARI DENGAN METODE PEMBELAJARAN KONTEKSTUAL PADA SISWA KELAS II SDN 06 KOTO BARU - melsi oktadiana yepita andila, dhea zafitri, maisita (Jurnal Dharma PGSD, 2025)
This research was conducted with the aim of helping second-grade students at SDN 06 Koto Baru better understand the meaning of the symbols of Pancasila and apply them in their daily lives. The learning approach used was adapted to the students’ real-life experiences and environment, making the learning process feel more relevant and meaningful. Based on observations, many students still lacked a proper understanding of Pancasila values and had not yet demonstrated attitudes that reflect the principles of Pancasila. Therefore, this study was carried out as Classroom Action Research (CAR) consisting of two cycles. The implementation process included planning, action, observation, and reflection stages. Data were collected through classroom observations, documentation of learning activities, and learning outcome tests. The results of the study showed an improvement in students’ understanding of the Pancasila symbols as well as positive changes in their attitudes and behaviors, which began to reflect the values of Pancasila in their everyday lives.